Arquitectura del templo de San Nicolás y monasterio del Santo Sepulcro, desde la reconquista de Zaragoza hasta el siglo XIX: Architecture of the church of Saint Nicholas and the monastery of Holy Sepulchre, from the reconquest of Saragossa to the 19th century - Usón García, Ricardo (Artigrama, 2025)
ResumenEl monasterio del Santo Sepulcro de Zaragoza es un bello ejemplar de la arquitectura gótica regional del siglo XIV. Construido básicamente con ladrillo y conservado casi en su totalidad, responde a un proyecto de fray Martín de Alpartir, tesorero del arzobispo Lope Fernández de Luna, quien tras obtener de éste la adscripción del templo de San Nicolás –reedificado poco antes en el mismo formato– desarrolla un programa de tipología cisterciense cuya espectacular sala capitular –concebida como su mausoleo– singularmente evoca el mismo sepulcro jerosolimitano, convirtiéndose en el núcleo de la advocación conventual.  AbstractThe Monastery of the Holy Sepulchre in Zaragoza is an exquisite example of 14th century regional Gothic architecture. Constructed primarily of brick and almost entirely preserved, it was designed by Friar Martín de Alpartir, treasurer of Archbishop Lope Fernández de Luna. After securing from the archbishop the assignment of the San Nicolás temple –rebuilt shortly before in a similar style– Friar Martín developed a Cistercian-inspired design. The monastery's spectacular chapter house –conceived as a mausoleum– uniquely evokes the Holy Sepulchre in Jerusalem, serving as the central focus of the convent's dedication.KeywordsSaragossa, Architecture, Gothic, Mausoleum, Sepulchre, Jerusalem.